2019
DOI: 10.1128/mbio.00356-19
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Replacement of Acinetobacter baumannii Strains Accompanied by Changes in Lipooligosaccharide Loci and Resistance Gene Repertoire

Abstract: The population structure of health care-associated pathogens reflects patterns of diversification, selection, and dispersal over time. Empirical data detailing the long-term population dynamics of nosocomial pathogens provide information about how pathogens adapt in the face of exposure to diverse antimicrobial agents and other host and environmental pressures and can inform infection control priorities. Extensive sequencing of clinical isolates from one hospital spanning a decade and a second hospital in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 60 publications
(75 reference statements)
7
27
0
Order By: Relevance
“…These results follow the molecular Koch's postulates modified for loss-of-function driving virulence [20], indicating that the bacterial capsule is a primary driver of virulence, as demonstrated across multiple clinical isolates and isogenic strain pairs. BLAST analysis confirmed that this insertion element has previously been characterized as ISAba13 and is present in a variety of A. baumannii clinical isolates, and other work confirms that frequent transposonmediated disruption of genes contributes significantly to A. baumannii virulence in the form of outer molecule structural variation [21], metabolic function, and antimicrobial resistance [22,23].…”
Section: Discussionsupporting
confidence: 75%
“…These results follow the molecular Koch's postulates modified for loss-of-function driving virulence [20], indicating that the bacterial capsule is a primary driver of virulence, as demonstrated across multiple clinical isolates and isogenic strain pairs. BLAST analysis confirmed that this insertion element has previously been characterized as ISAba13 and is present in a variety of A. baumannii clinical isolates, and other work confirms that frequent transposonmediated disruption of genes contributes significantly to A. baumannii virulence in the form of outer molecule structural variation [21], metabolic function, and antimicrobial resistance [22,23].…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, the decrease in HA respiratory, urinary, and blood isolates to near-0 levels unmasked an endemic occurrence of nHA isolates with epidemiologic features similar to nHA isolates from non-BJC1 hospitals (ie, urinary and SST/MSK isolates with ~40% CRAb rates). Consistent with the existence of nHA reservoirs, genomic analysis of A. baumannii isolates in another US Midwest medical center suggested that transmissible isolates at 2 independent hospitals originated from a single, external, nonhospital pool [13]. The location of outpatient Abc pools, their trafficking into hospital environments, and the impact of nHA strains on local Abc disease require further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…clinical strains were used to test sulbactam or sulbactam in combination with avibactam or relebactam ( Table S1 ). Among the included strains 152 were A. baumannii , including previously well-characterized strains such as AB5075, AB0057 and ABUH702 [ 40 , 41 , 42 ], and 35 corresponded to non- baumannii species. Among these isolates, 4 were non-ESBL/non-CRAB, 7 were ESBL producing, while 176 were carbapenem-resistant strains.…”
Section: Methodsmentioning
confidence: 99%